What's on your hard drive?. - O'Hanlon, Charlene (ACM queue : architecting tomorrow's computing., 2006)
One of the interesting things about WOYHD is seeing which tools developers seem to rely on most heavily. Despite the large amount of software available, a few core programs appear again and again. Even more intriguing is that developers often dislike these very same tools. Read on to discover what others think about the software you depend on. Feel like expressing your own opinion? Log on to http://www.acmqueue.com!